PENGEMBANGAN PARIWISATA HALAL DI PULAU PENYENGAT PROVINSI KEPULAUAN RIAU - Riska Destiana; Kismartini Kismartini (Dialogue : Jurnal Ilmu Administrasi Publik, 2020)
Penyengat Island in Riau Islands Province was appointed by the Ministry of Tourism as one of the leading halal tourism destinations. The development of halal tourism on Penyengat Island requires strategies that can increase Muslim tourist arrivals. This article aims to analyze alternative strategies for the development of halal tourism in Penyengat Island so that the number of tourist visits can increase and the application of the concept of halal tourism in Penyengat Island can be implemented, so as to obtain the recommended strategy. This research uses a qualitative descriptive approach through literature study with the use of journals that are in accordance with the research topic. The alternative policy evaluation uses evaluation criteria in the form of technical feasibility, economic feasibility, political feasibility and administrative feasibility. There are three alternative policies that can be implemented for the development of halal tourism on Penyengat Island, namely branding and marketing; easy access and visa; and the provision of Muslim tourist-friendly facilities. The policy recommendation is the provision of friendly facilities for Muslim tourists that can creat comfortable for Muslim tourists.